Variable Speed DC Generator Voltage Control using a Multistage Comparator - Augustinus Sujono; Feri Adriyanto; Hari Maghfiroh; Joko Slamet Saputro; Agus Ramelan (Journal of Electrical, Electronic, Information, and Communication Technology, 2021)
DC generator with variable rotation will produce uncontrolled voltage, causing problems in its utilization. In this study, it is proposed to develop a voltage control on the generator, in order to produce a fairly controllable and reliable voltage, with an analog circuit using a multistage comparator. Control of the generator output voltage is carried out by adjusting the field current from a separate voltage source which is forwarded to the resistance which is regulated based on the generator output voltage level with a multilevel comparison system. The results obtained are the output voltage ranges from 26 to 30 Volts and the output current ranges from 3 to 20 Amperes. This provides operational safety for the generator and battery. This technology can be used in dc generator systems in automotive engines, windmills, and other power plants.